AI IN EDUCATION AND SKILL DEVELOPMENT FOR SUSTAINABLE DEVELOPMENT IN UTTARAKHAND - Dr Vinod Singh Negi; Mr Sumit Joshi; Mr. Mayank Tomar (International Educational Journal of Science and Engineering, 2025)
AI IN EDUCATION AND SKILL DEVELOPMENT FOR SUSTAINABLE DEVELOPMENT IN UTTARAKHAND